Blockchain as a Tool for Transforming the Process of Assessing Intellectual Property Objects - V. A. Bezuglaya; S. F. Kugan (Цифровая трансформация)
The article provides an analysis of the integration of blockchain technologies into the methodology of in tellectual property valuation, which is a significant step towards the digital transformation of existing approaches in the field of intellectual property valuation. The opportunities and challenges associated with the use of modern digital technologies to improve the efficiency of intellectual property valuation are identified. The impact of block chain solutions on valuation processes is studied with an emphasis on transparency and protection of rights. New valuation models based on smart contracts are considered to create fairer mechanisms for distri buting royalties, key challenges associated with legal regulation and technical aspects of implementing blockchain technologies are identified. The need to develop uniform standards and protocols for the global integration of valuation processes is determined. Key problems associated with legal regulation and technical aspects of imp lementing blockchain technologies in the valuation process are noted. The need to develop uniform standards and protocols for the glo bal integration of this area is emphasized. The potential of blockchain technologies as a catalyst for innovation and cooperation in the international arena is shown, opening up new horizons for further research and practical applications in the field of intellectual property.